MORPHINE-ENHANCED APOPTOSIS IN SELECTIVE BRAIN REGIONS OF NEONATAL RATS - Bajic, Dusica (2013)
Prolonged neonatal opioid exposure has been associated with: antinociceptive tolerance, long-term neurodevelopmental delay, cognitive, and motor impairment. Morphine has also been shown to induce apoptotic cell death in vitro studies, but its in-vivo effect in developing rat brain is unknown. Thus, we hypothesized that prolongued morphine administration in neonatal rats in a model of antinociceptive tolerance and dependence is associated with increased neuroapoptosis. We analyzed neonatal rats from the following groups (1) naïve group (n=6); (2) control group (normal saline (NS), n=5), and (3) morphine group (n=8). Morphine sulfate or equal volume of NS was injected subcutaneously twice daily for 6.5 days starting on postnatal day (PD) 1. Development of antinociceptive tolerance was confirmed by Hot Plate test on the 7(th) day. Evidence of neuronal and glial apoptosis was determined by cleaved caspase-3immunofluorescence combined with specific markers. At PD7, morphine administration after 6 ½ days significantly increased the density of apoptotic cells in the cortex and amygdala, but not in the hippocampus, hypothalamus, or periaqueductal gray. Apoptotic cells exhibited morphology analogous to neurons. Irrespective of the treatment, only a very few individual microglia but not astrocytes were caspase-3 positive. In summary, repeated morphine administration in neonatal rats (PD1-7) is associated with increased supraspinal apoptosis in distinct anatomical regions known to be important for sensory (cortex) and emotional memory processing (amygdala). Brain regions important for learning (hippocampus), and autonomic and nociceptive processing (hypothalamus and periaqueductal gray) were not affected. Lack of widespread glial apoptosis or robust glial activation following repeated morphine administration suggests that glia might not be affected by chronic morphine at this early age. Future studies should investigate long-term behavioral sequelae of demonstrated enhanced apoptosis associated with prolonged morphine administration in a neonatal rat model.